2004
DOI: 10.1016/s0074-7696(04)40002-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Distribution and Functions of P2 Receptor Subtypes in Different Systems

Abstract: This review is aimed at providing readers with a comprehensive reference article about the distribution and function of P2 receptors in all the organs, tissues, and cells in the body. Each section provides an account of the early history of purinergic signaling in the organ?cell up to 1994, then summarizes subsequent evidence for the presence of P2X and P2Y receptor subtype mRNA and proteins as well as functional data, all fully referenced. A section is included describing the plasticity of expression of P2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
628
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 709 publications
(645 citation statements)
references
References 2,427 publications
5
628
1
11
Order By: Relevance
“…All known subtypes of P2Y receptors are expressed in the CNS with variable distribution among different cell types (i.e. neurons, astrocytes, microglia, oligodendrocytes) (Burnstock and Knight, 2004). These receptors are activated during pathological conditions and participate in neuroinflammation in many different ways.…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…All known subtypes of P2Y receptors are expressed in the CNS with variable distribution among different cell types (i.e. neurons, astrocytes, microglia, oligodendrocytes) (Burnstock and Knight, 2004). These receptors are activated during pathological conditions and participate in neuroinflammation in many different ways.…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 99%
“…While P2Y 11 mRNA can be found in the nervous system (Burnstock and Knight, 2004), and these receptors are expressed on human immunocytes and regulate neurotrophil apoptosis (Communi et al, 1999;Vaughan et al, 2007), a potential immunomodulatory role in the CNS may also be hypothesized. P2Y 12 receptors are G i -coupled receptors and well-known as the target site of widely used antithrombotic drugs such as clopidogrel or ticagrelor, and are therefore of considerable interest to cardiovascular medicine.…”
Section: The Role Of P2y Receptors In Neuroinflammationmentioning
confidence: 99%
“…Recently, highly selective and potent P2X 7 R antagonists have been identified [10] with one of these showing initial positive results in Phase II clinical trials for rheumatoid arthritis [11]. The case for P2X 4 R remains tentative, largely due to the absence of selective P2X 4 R antagonists and the complicating presence of P2X 7 R, which is generally co-expressed with P2X 4 R in macrophages and microglia [3]. P2X 4 R does not appear to couple to any of the same downstream signalling cascades as has been demonstrated for P2X 7 R but studies with P2X 4 R gene-deleted mice have revealed abrogation of tactile allodynia in animal models of inflammatory (formalin-induced) and neuropathic (nerve section) pain via yet-to-be identified alterations in microglial functions [12][13][14].…”
mentioning
confidence: 99%
“…Purine receptors Introduction Extracellular ATP acts as a ''danger signal'' when it is released from cells during tissue damage and inflammation; it acts on metabotropic (G-protein coupled) P2Y and ionotropic (cation channel) P2X purinergic receptors to affect several inflammatory and immune responses [1,2]. There are seven members of the P2X receptor family (P2X 1-7 R) that show widespread distribution in both neuronal and non-neuronal tissues [3]. Two of these seven members, P2X 4 R and P2X 7 R, have generated increasing interest as potential anti-inflammatory drug targets [2,4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation